Postpartum psychiatric disorders and subsequent live birth: a population-based cohort study in Denmark. Issue 4 (29th March 2020) - Liu, X; Plana-Ripoll, O; Ingstrup, K G; Agerbo, E; Skjærven, R; Munk-Olsen, T
Abstract: STUDY QUESTION: Are women with a history of first-onset postpartum psychiatric disorders after their first liveborn delivery less likely to have a subsequent live birth? SUMMARY ANSWER: Women with incident postpartum psychiatric disorders are less likely to go on to have further children. WHAT IS KNOWN ALREADY: Women are particularly vulnerable to psychiatric disorders in the postpartum period. The potential effects of postpartum psychiatric disorders on the mother's future chances of live birth are so far under-researched. STUDY DESIGN, SIZE, DURATION: A population-based cohort study consisted of 414 571 women who had their first live birth during 1997–2015. We followed the women for a maximum of 19.5 years from the date of the first liveborn delivery until the next conception leading to a live birth, emigration, death, their 45th birthday or 30 June 2016, whichever occurred first. PARTICIPANTS/MATERIALS, SETTING, METHODS: Postpartum psychiatric disorders were defined as filling a prescription for psychotropic medications or hospital contact for psychiatric disorders for the first time within 6 months postpartum. The outcome of interest was time to the next conception leading to live birth after the first liveborn delivery. Records on the death of a child were obtained through the Danish Register of Causes of Death. Cox regression was used to estimate the hazard ratios (HRs), stratified by the survival status of the first child. MAIN RESULTS AND THE ROLE OF CHANCE: Altogether, 4327 (1.0%) women experienced postpartum psychiatric disorders after their first liveborn delivery. The probability of having a subsequent live birth was 69.1% (95% CI: 67.4–70.7%) among women with, and 82.3% (95% CI: 82.1–82.4%) among those without, postpartum psychiatric disorders. Women with postpartum psychiatric disorders had a 33% reduction in the rate of having second live birth (HR = 0.67, 95% CI: 0.64–0.69), compared to women without postpartum psychiatric disorders. The association disappeared if the first child died (HR = 1.01, 95% CI: 0.85–1.20). If postpartum psychiatric disorders required hospitalisations, this was associated with a more pronounced reduction in live birth rate, irrespective of the survival status of the first child (HR = 0.54, 95% CI: 0.47–0.61 if the first child survived, and HR = 0.49, 95% CI: 0.23–1.04 if the first child died). LIMITATIONS, REASONS FOR CAUTION: The use of population-based registers allows for the inclusion of a representative cohort with almost complete follow-up. The large sample size enables us to perform detailed analyses, accounting for the survival status of the child. However, we did not have accurate information on stillbirths and miscarriages, and only pregnancies that led to live birth were included. WIDE IMPLICATIONS OF THE FINDINGS: Our study is the first study to investigate subsequent live birth after postpartum psychiatric disorders in a large representative population. The current study indicates that postpartum psychiatric disorders have a significant impact on subsequent live birth, as women experiencing these disorders have a decreased likelihood of having more children. However, the variations in subsequent live birth rate are influenced by both the severity of the disorders and the survival status of the first-born child, indicating that both personal choices and decreased fertility may have a role in the reduced subsequent live birth rate among women with postpartum psychiatric disorders. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the Danish Council for Independent Research (DFF-5053-00156B), the European Union's Horizon 2020 research and innovation programme under the Marie Sklodowska-Curie grant agreement No. 837180, AUFF NOVA (AUFF-E 2016-9-25), iPSYCH, the Lundbeck Foundation Initiative for Integrative Psychiatric Research (R155-2014-1724), Niels Bohr Professorship Grant from the Danish National Research Foundation and the Stanley Medical Research Institute, the National Institute of Mental Health (NIMH) (R01MH104468) and Fabrikant Vilhelm Pedersen og Hustrus Legat. The authors do not declare any conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.